Large-area alginate/PEO-PPO-PEO hydrogels with thermoreversible rheology at physiological temperatures. (17th January 2018) - Quah, Suan P.; Smith, Andrew J.; Preston, Alyssa N.; Laughlin, Scott T.; Bhatia, Surita R.
Abstract: Alginate hydrogels have shown great promise for applications in wound dressings, drug delivery, and tissue engineering. This report details the fabrication and rheological properties of a multicomponent hydrogel consisting of alginate and poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (PEO-PPO-PEO) triblock copolymers, and the achievement of thick, castable gels with tunable, thermoreversible behavior at physiological temperatures. PEO-PPO-PEO triblock copolymers can form temperature-sensitive hydrogels that exist as liquids at low temperatures and soft solids at high temperatures. In this work, we have employed PEO-PPO-PEO triblock copolymers to impart thermoresponsive properties to alginate hydrogels in the form of a multicomponent hydrogel. These systems can transition between a weak gel and a stiff gel, with a corresponding increase in the viscoelastic moduli of approximately two orders of magnitude as temperature is increased. The temperatures corresponding to the upper and lower boundaries of the stiff gel region, as well as the storage modulus at physiological temperatures (e.g., 36–40 °C), can be controlled through the PEO-PPO-PEO concentration. Optically clear gels that are homogeneous on the microscale can be fabricated in a scalable manner to create flat, large-area thick films, making these systems favorable for applications in wound healing, soft tissue repair, and biomedical device coatings. Graphical abstract: Highlights: We report alginate-based gels with thermoresponsive rheology. Transitions in the rheology are observed at physiological temperatures. Gels can be cast as clear thick films for wound healing and soft tissue repair.